The Role of Villagers' Social Innovations in Advocacy Village Tourism Through Involvement of Study Activities in Village Tourism - Lusi Suwandari; Devani Laksmi Indyastuti; Meutia Karunia Dewi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2022)
This study aims to determine the positive relationship between social innovation, involvement, and advocacy tourism in the villagers Community. Active support from the village community can be very important for successful tourism development if villagers become more aware of the attractive characteristics of the area and are involved in developing sustainable tourism promotion in Village. In this study, a hypothesis test of the relationship between social innovation and advocacy tourism through community involvement will be conducted. To get a comprehensive picture, the researcher will collect a research sample of 100 villagers who have the criteria for the age of 18 to 50 years and are familiar with social media. Respondents will fill out a questionnaire and answers from respondents will be analyzed using path analysis to test hypotheses.